Polyploid giant cancer cells and cancer progression - Zhou, Xinyue; Zhou, Mingming; Zheng, Minying; Tian, Shifeng; Yang, Xiaohui; Ning, Yidi; Li, Yuwei; Zhang, Shiwu (Frontiers in Cell and Developmental Biology, 2022)
Polyploid giant cancer cells (PGCCs) are an important feature of cellular atypia, the detailed mechanisms of their formation and function remain unclear. PGCCs were previously thought to be derived from repeated mitosis/cytokinesis failure, with no intrinsic ability to proliferate and divide. However, recently, PGCCs have been confirmed to have cancer stem cell (CSC)-like characteristics, and generate progeny cells through asymmetric division, which express epithelial-mesenchymal transition-related markers to promote invasion and migration. The formation of PGCCs can be attributed to multiple stimulating factors, including hypoxia, chemotherapeutic reagents, and radiation, can induce the formation of PGCCs, by regulating the cell cycle and cell fusion-related protein expression. The properties of CSCs suggest that PGCCs can be induced to differentiate into non-tumor cells, and produce erythrocytes composed of embryonic hemoglobin, which have a high affinity for oxygen, and thereby allow PGCCs survival from the severe hypoxia. The number of PGCCs is associated with metastasis, chemoradiotherapy resistance, and recurrence of malignant tumors. Targeting relevant proteins or signaling pathways related with the formation and transdifferentiation of adipose tissue and cartilage in PGCCs may provide new strategies for solid tumor therapy.